Stress and Coping Strategies among Nurses and Midwives during Assisted Vaginal Delivery in Pregnant Women with COVID-19: A Cross-sectional Study - R Bagavathi; Binu Mathew; Shivangi Mudgal; Ranjana Kumari; Sapna Chopra (Journal of Public Health and Primary Care)
Background: COVID-19 pandemic was the most challenging issue which has induced unprecedented ramifications all over the world. During the pandemic, nurses and midwives were the pillars of health-care sector where they provide care to the patients, assist vaginal delivery, and provide emotional support too. However, psychological well-being of health-care professionals was somewhere lost. There is a lack of research regarding stress level and coping strategies among nurses and midwives within East Central India. Hence, the aim of the study was to assess the stress and coping strategies among nurses and midwives during assisted vaginal delivery among COVID-19 pregnant women. Design: A cross-sectional study was conducted among nurses and midwives who assisted vaginal delivery of COVID-19-affected pregnant women at a tertiary care hospital in East Central India. Data were collected through a validated online self-structured questionnaire; the COVID-19 Stress Scale was divided into five subdomains. Results: Data were analyzed using Chi-square and Spearman’s correlation coefficient. Findings revealed that majority (72%) of nurses and midwives were experiencing moderate stress while 65% had high level of coping strategies to be used during assisted vaginal delivery. A significant correlation was found between few domains of stress level and coping strategies (r = 0.260–0.302). Demographic variables were significantly associated with level of coping strategies. Conclusion: Majority of nurses and midwives experienced stress with high usage of coping strategies. However, evidence clearly mentioned that COVID-19 pandemic was the most challenging and devastating period, so health-care sector was the hummock for the population. However, it is recommended to make aware the people about hygiene taking utmost holistic care for nurses and midwives. It is vital to take emotional resilience into consideration for unpredictable future circumstances. Stress management program should be applied as an immediate measure to address the level of stress and its effectiveness should be checked longitudinally, with consideration of families and peers as well as nurses and midwives themselves.